MAKNA IDIOM DALAM 12 LIRIK LAGU KARYA CALUM SCOTT - SABAN, WINDA EKA LYANTO; JANSEN, FRIEDA TH.; RAMBING, ROSALINA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThis research aims to identify, classify, and analyze the idioms based on their forms and meanings. The descriptive method is used in this research, and the data have been taken from a Calum Scotts song lyrics and analyzed based on the theory of Boatner and Gates. The result of this research shows there are many in various idiom?s forms. Found in the lyricsthose are idioms that classified informs, lexemic idioms, which connects of four classes they are verbal idioms,nominal idioms, adjective idioms, and adverb idioms, phrases idioms, proverb and the writer didn?t find frozen form idiom in this song.This research can provide knowledge about the meaning of idioms in semantic studies, especially for readers, and can help students of the Faculty of Humanities, especially students majoring in English literature to examine idioms using different objects, also, this research can be used as a reference for further research. Key words Idiom Form and Meaning, semantics Analysis, The song lyrics of  Calum scott.